Churchill and America - Gilbert, Martin 1936- (Free Press, 2005)
Gilbert tells the intensely human story of Winston Churchill's profound connection to America, a relationship that resulted in an Anglo-American alliance that has stood at the center of international relations for more than a century. Churchill, whose mother, the daughter of a leading American entrepreneur, was born in Brooklyn in 1854, spent much of his seventy adult years in close contact with the United States. In two world wars, his was the main British voice urging the closest possible cooperation with the U.S. Churchill first visited in 1895, when he was twenty-one. During three subsequent visits before the Second World War, he traveled widely and formed a clear understanding of both the physical and moral strength of Americans. Gilbert explores how Churchill's rapport with this country resulted in no less than the liberation of Europe and the preservation of European democracy and freedom.--From publisher description.